First principles Investigation on the elastic properties of Mg, Ca, K-decorated planar aluminene - Villagracia, Al Rey C. (Animo Repository, 2019)
With 2D materials rising as candidates for hydrogen storage media, it is important to understand their mechanical properties. Using density functional theory, this study investigated Mg, Ca, and K as dopants to aluminene to determine their effects on its physical properties. Calculations were carried out using Vienna ab initio simulation package (VASP) with Perdew-Burke-Erzernhof (PBE) as generalized gradient approximation (GGA) exchange correlation functional. The brillouin zone sampling was set to 8 by 8 by 1 mesh size, and the energy cut-off of 450 eV. Density functional theory were employed to determine the best possible site (either at the hollow, bridge, or top) for adsorption, and to obtain stress-strain graphs. Among the three sites it was found that the Mg, Ca, and K decorations all prefer the hollow site for adsorption. With its shortest distances also located at that site. As for the stress-strain graph it was found to have a low strain as seen by its linear behavior. Lastly obtaining the slope gave the elastic modulus and stiffness, and with the introduction of the decorations at the hollow site increases its property values. Results showed better stiffness and modulus compared to pristine aluminene. © 2019 IEEE.